Dynamics and Diagnosis of Independent Thinking Processes of Students (on the Example of the First Teenagers) - Buriyeva, Kibrio; Omonovich, Khimmataliev Dustnazar (Angstrom Centre of Education, 2024)
The article describes, creative, modular technologies for improving the socio-psychological mechanisms of the development of independent thinking of adolescent students are included in the practice. The following methodologies were used, which were considered subtests of the scientific and theoretical sources on the topic, comparative analysis, observation, question and answer, conversation, Wexler and Amtxauer methodologies: methodology